The best selection of strategic plans in balanced scorecard using multi-objective decision making model - Dodangeh, Javad; Mohd Yusuff, Rosnah; Jassbi, Javad (Academic Journals, 2011)
In an increasingly competitive business environment, many organizations have adopted the strategic planning approach in an attempt to achieve excellence in business. Implementation of appropriate strategies plays an important role for organizations' success. Balanced scorecard is an appropriate tool used for designing operational strategies. However, one of the balanced scorecard problems is its selection in strategic plans' performance. In this paper, a model was established for the selection of strategic plans in “balanced scorecard” using “goal programming model” which is one of the multi-objective decision making models. So, using the consensus of organizations’ managers and experts' opinions, the measures and general objectives of the four perspectives are first determined in BSC, and then, using experts' opinions and taking the relative importance of decision makers' opinions into consideration, by using “goal programming model”, the performances of strategic plans are selected in the BSC model. The results show that the introduced method is more reliable and acceptable and the experts verify the model for selecting strategic plans in the operation of BSC. The introduced method was used in a study and the extracted results from it were analyzed from different points of view. However, in this article, initiatives are called strategic plans.